Optimization of xylanase biosynthesis by Aspergillus japonicus isolated from a Caatinga area in the Brazilian state of Bahia - Simões, Maria Lúcia Garcia [UNESP]; Tauk-Tornisielo, Samia Maria [UNESP] (My University, 2006)
The objective of this research was to investigate the potential of xylanase production by Aspergillus japonicus and to determine the effects of cultivation conditions in the process, aiming toward optimization of enzyme production. The best temperature, as well as the best carbon source, for biomass production was determined through an automated turbidimetric method (Bioscreen-C). The enzyme activity of this fungus was separately evaluated in two solid substrates (wheat and soybean bran) and in Vogel medium, adding other carbon sources. Temperature effects, cultivation time, and spore concentrations were also tested. The best temperature for enzyme and biomass production was 25°C; however, the best carbon source for growth (determined by the Bioscreen C) did not turn out to be a good inducer of xylanase production. Maximum xylanase activity was achieved when the fungus was cultivated in wheat bran (without the addition of any other carbon source) using a spore concentration of 1 × 107 spores/mL (25°C, pH 5.0, 120 h). A. japonicus is a good xylanase producer under the conditions presented in these assays. © 2006 Academic Journals.
Keywords: Aspergillus japonicus; Enzyme optimization; Xylanase activity; carbon; xylan endo 1,3 beta xylosidase; Aspergillus; aspergillus japonicus; biomass production; biosynthesis; bran; Brazil; carbon source; concentration (parameters); enzyme activity; enzyme synthesis; fungus isolation; nonhuman; soybean; species cultivation; temperature; turbidimetry; wheat; Fungi; Glycine max; Triticum aestivum